Rescue - Haas, Jessie (Honesdale, Pennsylvania : Boyds Millls Press, an imprint of Highlights, 2018)
When Chess moves near Joni, their differing opinions have Joni defending her family's farm, and she must find the courage to stand up to Chess when she decides to "rescue" the minature horses from a nearby farm.
Accelerated Reader
Keywords: Animal welfare -- Juvenile fiction; Horses -- Juvenile fiction; Farms -- Juvenile fiction; Friendship -- Juvenile fiction; Animal welfare -- Fiction; Farms -- Fiction; Friendship -- Fiction; Horses -- Fiction; JUVENILE FICTION -- Animals -- Horses; JUVENILE FICTION -- Legends, Myths, Fables -- Farm & Ranch Life; JUVENILE FICTION -- Social Themes -- Friendship; Animal welfare; Farms; Friendship; Horses; Animal welfare -- Fiction; Horses -- Fiction; Farms -- Fiction; Friendship -- Fiction; Animal fiction; Fiction; Juvenile works; Animal fiction